2013
DOI: 10.1016/j.cemconcomp.2012.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colloidal nanosilica on rheological and mechanical properties of fly ash–cement mortar

Abstract: The present study is aimed at investigating the combined effects of colloidal nanosilica (CNS) and fly ash on the properties of cement-based materials. The fresh and hardened properties of mixtures with CNS of 10 nm size and two Class F fly ashes were evaluated. Results revealed that CNS accelerates the setting of fly ash-cement systems by accelerating cement hydration, while fly ash can offset the reduction in fluidity caused by CNS. The early-age strength gain (before 7 d) of fly ash-cement systems was impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(85 citation statements)
references
References 31 publications
8
71
2
4
Order By: Relevance
“…Influence of selected activating methods on hydration processes... relationship between intensity of strength gain and time was also observed in [88].…”
Section: Silica and Aluminosilicate Pozzolanic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of selected activating methods on hydration processes... relationship between intensity of strength gain and time was also observed in [88].…”
Section: Silica and Aluminosilicate Pozzolanic Materialsmentioning
confidence: 99%
“…This material is fine-grained and may cause deterioration of fluidity; however, this effect may be compensated by spherical grains of fly ash [87,88]. Accelerating action of small amount of silica fume on early hydration of high volume fly ash mixture may be manifested in changes of shape of heat release curve while improvement in pozzolanic activity by reduction in Ca(OH) 2 basing on TG/ DTG results.…”
Section: Silica and Aluminosilicate Pozzolanic Materialsmentioning
confidence: 99%
“…The previous studies showed that the dispersion method of the NS particles affects the workability of cement mortar, the rate and extent of cement hydration as well as the structural, physical and mechanical properties of the fresh and hardened cement composites 11,[30][31][32][33] . Some authors have concluded that the appropriate percentage of NS must be small (1-5 wt%) to avoid agglomeration of particles during mixing [12][13][14][15][16] , while others have indicated that properties can also be improved with higher dosages up to approximately 10 wt% if these nanoparticles are successfully dispersed in the initial cementious mixture 7,12,17,29 . Second problem related with using NS in a cement mixture is the decrease in fluidity, due to its high surface area and increased water demand [29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, supplementary cementing materials (SCMs) with pozzolanic or hydraulic properties have been particularly attractive compounds or mixtures which partially replace ordinary Portland cement required for a cement-based composite 5,6 . The most widely used SCMs in cement composites are fly ash (FA) and silica fume (SF), that are obtained as the by-products of the coal industry and the silicon-ferrosilicon industries, respectively 7,8 . FA and SF enhance mainly the long-term strength and durability properties of cement composites owing to their pozzolanic reactions with calcium hydroxide formed during the hydration of calcium silicates [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation